Using the MMPI-2 College Maladjustment Scale in a Canadian University Setting - Stewart, Donald W. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study reports on the initial results of a validation study of the College Maladjustment (Mt) scale from the recently revised Minnesota Multiphasic Personality Inventory. In a Canadian university setting, the Mt scale was completed by three groups of students (personal counselling; vocational counselling; scholarship recipients) intended to reflect a range of psychological functioning. It was predicted that students presenting for personal counselling would obtain higher scores than students presenting with vocational concerns or earning a scholarship. The results indicated that students in the personal counselling condition scored significantly higher than students in the other conditions. Implications for the validity of the scale and its use in a counselling service are discussed.